JURNAL DIRI SEBAGAI MEDIA KONSELING AUTOBIOGRAFIS DALAM PENERAPAN TEKNIK SELF-MANAGEMENT UNTUK MEREDUKSI PERILAKU MEMBOLOS SISWA - Melady, Dian; Romlah, St; Qomariyah, Lailatul (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2024)
Truancy in students is a challenge in education that can disrupt academic achievement and character development. One approach to reducing this behavior is the use of self-management techniques, which involve self-regulation to improve behavioral control and goal achievement. This article aims to explore the application of self-management techniques to reduce truancy in students through qualitative descriptive methods, using observation and interview data collection techniques. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing. The findings of this article indicate that self-management techniques are effective in helping students reduce truancy. This can be considered successful, as there are significant changes in students, such as increased self-awareness and increased motivation to attend school.